Case Report: Neuronal Intranuclear Inclusion Disease With Oromandibular Dystonia Onset - Deng, Wei-Ping; Yang, Zhao; Huang, Xiao-Jun; Jiang, Jing-Wen; Luan, Xing-Hua; Cao, Li (Frontiers in Neurology, 2021)
Background: Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disease. Because of variable clinical manifestations, NIID was often misdiagnosed. According to published case reports, the common clinical manifestations of NIID include dementia, muscle weakness，autonomic impairment, sensory disturbance, rigidity, ataxia convulsions, etc. However, no cases of oromandibular dystonia were mentioned. Case Presentation: We describe a case of 58-year-old woman presenting with mouth involuntary chewing initially. She started to show hand tremors, ataxia and walking instability until two years later. Diffusion-weighted imaging showed high intensity signal along corticomedullary junction. Fluid-attenuated inversion recovery imaging showed white matter hyperintensity. EMG indicated peripheral nerve degeneration. Neuropsychological testing showed memory loss. Finally, skin biopsy and GGC repeat expansions in the NOTCH2NLC (Notch 2 N-terminal like C) gene confirmed the diagnosis of NIID. Conclusion: This case demonstrated that oromandibular dystonia could be the first symptom of NIID. This case report provides new clinical characteristics of NIID and broads clinical spectrum.